Regional structural control on the distribution of world‐class gold deposits: An overview from the Giant Jiaodong Gold Province, China. (30th March 2018) - Deng, Jun; Yang, Li‐Qiang; Li, Rui‐Hong; Groves, David I.; Santosh, M.; Wang, Zhong‐Liang; Sai, Sheng‐Xun; Wang, Si‐Rui
Abstract : The Jiaodong gold province in northeastern China is the country's premier gold resource and globally one of the most important gold provinces. The late Early Cretaceous gold metallogeny in this belt remains an enigma as it is hosted in the Archean Jiaobei Terrane of the North China Block and, to a lesser extent, within the Palaeoproterozoic Sulu Terrane of the South China Block. The driving force for widespread Late Jurassic and Early Cretaceous granitic magmatism, the switchover from a compressional to extensional tectonic regime, and gold mineralization are considered to be a combination of plate subduction with lithospheric delamination and consequent asthenospheric upwelling. Although many aspects related to the genesis of the gold deposits in Jiaodong have been resolved, the spatial distribution of the world‐class gold deposits in this belt, which is of vital importance to brownfields and greenfields exploration, has been poorly understood in terms of the structural evolution of the province. In the northwestern segment of the Jiaobei Terrane, the world‐class gold deposits of Sanshandao in the west, through Jiaojia, to Linglong in the east define a broadly E–W corridor. This corridor links a series of east‐verging jogs on ore‐controlling NNE‐trending oblique‐slip faults that are subparallel to an lithospheric‐scale Tan‐Lu Fault to the west. There is cryptic evidence that these jogs line up in the E–W trend due to reactivation of Palaeoproterozoic to Mesozoic faults and folds that were part of the structural architecture of the terranes prior to the gold event. These jogs induced deviations in the local principal stresses relative to regional equivalent stresses, with resultant heterogeneous strain, increased rock permeability, and focussed ore‐fluid ingress. Both disseminated/microbreccia‐stockwork and vein‐type gold deposits formed in this corridor, with the former being predominant and the latter having a higher gold grade. In contrast, predominant vein‐type gold deposits in the eastern segment of the Jiaobei and Sulu terranes tend to form N–S corridors. These vein‐type ores may relate to rotational strain induced by movement on pairs of more linear NNE‐trending faults with the same kinematic movement sense.